Answer:
The result of adding the two equations is:
![8x=32](https://img.qammunity.org/2021/formulas/mathematics/college/fc7hictrsznk7psalgqusevpkv0a2jhu6h.png)
And the solution to the system is (4, 6).
Explanation:
We are given the system of equations:
![\left\{ \begin{array} \ 2.5y+3x=27 \\ 5x-2.5y=5 \end{array}](https://img.qammunity.org/2021/formulas/mathematics/high-school/v21aov1ho8w48txr0hwlactyrtesqk1eq1.png)
We can solve by elimination. If we add the two equations together, we acquire:
![(2.5y+3x)+(5x-2.5y)=(27+5)](https://img.qammunity.org/2021/formulas/mathematics/high-school/22lfcpmiu1cxlvcdsgx6iv07j7kpzvc2sw.png)
Simplifying yields:
![(2.5y-2.5y)+(3x+5x)=(32)](https://img.qammunity.org/2021/formulas/mathematics/high-school/luo1wsjkn1spa2y494dk0gewm4pu02xtvl.png)
Combine like terms. Therefore, we the two equations are added together, we obtain:
![8x=32](https://img.qammunity.org/2021/formulas/mathematics/college/fc7hictrsznk7psalgqusevpkv0a2jhu6h.png)
Solve for x by dividing both sides by 8:
![x=4](https://img.qammunity.org/2021/formulas/mathematics/middle-school/a1fs70p5exgs68ljexkqkiueya3liaz52t.png)
With the value of x, we can solve for y. Using the first equation:
![2.5y+3x=27](https://img.qammunity.org/2021/formulas/mathematics/high-school/vhsthr0vhvfa8qxtqlr7fu4xv7tqof94bi.png)
Substitute 4 for x and solve for y:
![\displaystyle \begin{aligned} 2.5y + 3(4) & = 27 \\ \\ 2.5y + 12 & = 27 \\ \\ 2.5y & = 15 \\ \\ y & = 6 \end{aligned}](https://img.qammunity.org/2021/formulas/mathematics/high-school/8sdwizgpe82k40rlqbu1gw6ngkd9fhskc3.png)
In conclusion, our solution to the system is (4, 6).